The Role of Character Education in Shaping Student Work Ethic: Teacher and Parent Perspectives - Fitri, Meliana Araswati (Jurnal Ar Ro'is Mandalika (Armada), 2024)
Character education plays a crucial role in shaping students' work ethic and fostering positive attitudes towards work. This study explores the perspectives of teachers and parents regarding the role of character education in shaping students' work ethic. Using a qualitative approach and drawing upon literature review and library research, the study investigates various aspects of character education that contribute to the development of work ethic among students. The findings highlight the importance of character education in instilling values such as responsibility, diligence, perseverance, and integrity, which are essential components of a strong work ethic. Teachers and parents both recognize the significance of character education programs in schools and home environments in nurturing these values from an early age. Additionally, the study delves into the methods and strategies employed by educators and parents to integrate character education into students' daily lives, emphasizing the need for collaborative efforts between schools and families to reinforce character development consistently. The research also discusses challenges and barriers faced in implementing character education initiatives and suggests potential solutions to address these obstacles. Overall, the study underscores the pivotal role of character education in molding students' attitudes towards work and highlights the collaborative efforts needed between educators and parents to foster a strong work ethic among students.